Vegetable based intercropping system in pomegranate under hot arid region (Indian Journal of Arid Horticulture, 2021)
Field experiments were conducted at farmer's field in Charanwala branch of IGNP stage-II in Bikaner district of Rajasthan during rabi and kharif seasons of 2015-16 and 2016-17, respectively to study the productivity and economic returns of pomegranate based intercropping systems in one and half year old pre-bearing orchard of pomegranate (Punica granatum var. Bhagwa). There were five treatment combinations i.e. (i) Pomegranate + onion (Allium cepa)- Indian squash (Citrullus lanatus var. fistulosus ), (ii) Pomegranate + radish (Raphanus sativus)- cowpea (Vigna unguiculata), (iii) Sole onion- Indian squash, (iv) Sole radish- cowpea and (v) Sole pomegranate. Intercropping has positive effect on height, girth and canopy spread of pomegranate tree over its sole plantation. The annual system productivity in terms of onion equivalent yield (OEY) was maximum in sole onion-Indian squash system which was at par with inter-copping system of pomegranate + onion-Indian squash. Water productivity can be improved to 2.87 and 6.71 kg m3 in terms of economic yield (WPEY) and 130.5 and 378.6 Rs ha ̈ mm" in terms of gross return (WPGR) with intercropping system of pomegranate +radish- cowpea and pomegranate + onion- Indian squash, respectively as compared to sole pomegranate plantations. An additional income of Rs. 2.36 lakhs/ha/year can be obtained with intercropping system of pomegranate + onion- Indian squash and 0.49 lakhs/ha/year with pomegranate + radish- cowpea intercropping system over sole plantations of pomegranate.
Keywords: Economics; pomegranate; intercropping system; water productivity; yield